Anti-reflection coating solution for photovoltaic glass and coated glass with gradient film layer
Patent Information
- Application Number
- CN202611125798.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]本发明的目的在于提供一种光伏玻璃用减反射镀膜液,利用该镀膜液可以实现一次涂布形成具有梯度折射率的减反射膜层,而不需要借助多次镀膜来实现膜层折射率的梯度过渡,解决了现有多层镀膜工艺容易导致膜层分离,膜层间产生界面分界线,进而影响镀膜玻璃的外观和透光率的问题
本发明通过在减反射镀膜液中引入两种或多种物理学性质(密度、粒径)差异化的氧化物材料,利用沉降速率差,使得密度较高和/或粒径较大的氧化物材料(通常具有较高折射率)快速下沉,富集于靠近玻璃基板的底部;而真密度较低和/或粒径较小的氧化物材料(通常具有较低折射率)沉降慢,被排挤并滞留于湿膜上层;在后续的固化过程中这种由重力驱动形成的高折射率颗粒到低折射率颗粒的梯度结构被粘结剂原位固定,在单一的连续膜层中形成了力学上一体的折射率渐变层,而无需由多层膜构建折射率渐变的复合减反射膜层结构,从而消除了多层膜间易分层及易产生层间界面分界而影响镀膜玻璃外观和透光率的问题。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of photovoltaic glass technology, specifically to an anti-reflective coating liquid for photovoltaic glass, coated glass with a gradient film layer, and a method for preparing the same. Background Technology
[0002] As a key encapsulation material for solar cell modules, the transmittance of photovoltaic glass directly affects the power generation efficiency of the modules. To improve the transmittance of photovoltaic glass, an anti-reflective coating is usually applied to the surface of the glass substrate. In existing technologies, single-layer anti-reflective coatings (such as single-layer silica or porous silica films) can improve transmittance to a certain extent, but their anti-reflection effect is limited by a single refractive index, making it difficult to achieve optimal anti-reflection performance over a wide spectral range; the transmittance gain is usually no more than 2.5%. In addition, some technical solutions have attempted to use hollow silica nanoparticles to reduce the refractive index of the anti-reflective film. However, using only high-porosity hollow particles to form an anti-reflective film often results in insufficient mechanical strength, wear resistance, and weather resistance. Under harsh outdoor environments (such as wind, sand, high temperature, and high humidity), the film is prone to wear, peeling, or performance degradation. Furthermore, the prior art (CN117285834A) discloses a coating solution, which, although it discloses a light-transmitting material containing a hollow structure, aims to achieve light wave conversion and anti-reflection using a single light-transmitting material in conjunction with quantum dots. The light-transmitting material is designed as a homogeneous optical medium. The above scheme emphasizes that the light-transmitting material and rare earth doping must follow strict ratio requirements, which means that the formulation must be uniform and stable. Otherwise, imbalance in the ratio in different areas will cause performance differences. If the mixing is uneven (layering or sedimentation occurs), the local quantum dot concentration will deviate from the optimal range, thereby affecting the light transmittance and conversion efficiency. In fact, it implicitly implies the process goal of maintaining the uniform distribution of each component in the coating solution and avoiding layering / sedimentation. Even if unavoidable small particle sedimentation occurs during the curing process, it is regarded as a defect of uneven coating, rather than a controllable means that can be used to form a stable gradient refractive index structure. It does not address how to achieve an ideal gradient of refractive index from the substrate to the air interface through the design of the coating solution formulation itself, without the need for a complex multi-layer coating process. To achieve the ideal gradient of refractive index, existing technologies have to rely on multi-layer coating. However, this multi-layer coating method not only leads to problems such as easy peeling of the interlayer interface and complex processes, but also easily causes the problem of interface boundary lines between the layers, which in turn affects the appearance and light transmittance of the glass. Summary of the Invention
[0003] The purpose of this invention is to provide an antireflective coating liquid for photovoltaic glass. This coating liquid can achieve the formation of an antireflective film layer with a gradient refractive index in a single coating process, without the need for multiple coatings to achieve the gradient transition of the film layer's refractive index. This solves the problem that existing multi-layer coating processes are prone to causing film layer separation and the generation of interface boundaries between film layers, which in turn affects the appearance and light transmittance of the coated glass.
[0004] To achieve the above objectives, the present invention is implemented through the following technical solution: This invention provides an antireflective coating solution for photovoltaic glass, comprising a solvent, a film-forming component, and an oxide material dispersed in the solvent; wherein the film-forming component includes a binder and a leveling agent, and the oxide material comprises at least a first oxide material and a second oxide material with different densities and / or particle sizes; the density ρ1 of the first oxide material and the density ρ2 of the second oxide material satisfy |ρ1-ρ2|≥0.2g / cm³. 3 And / or the average particle size D1 of the first oxide material and the average particle size D2 of the second oxide material satisfy D1 / D2≥1.5 or≤0.67, the first oxide material and the second oxide material also have different refractive indices, the refractive indices of the first oxide material and the second oxide material are 1.20~1.48 respectively.
[0005] Specifically, this invention uses two oxide materials with different densities and / or particle sizes in the formulation of the antireflective coating solution, so that the two materials can spontaneously generate a difference in gravitational settling rate in the wet film formed by the coating solution before the binder cures, forming a settling arrangement with a gradient of concentration from the bottom to the top of the wet film. During the subsequent curing process, this gradient structure of high-refractive-index particles to low-refractive-index particles formed by gravity is fixed in situ by the binder, forming a mechanically integrated refractive index gradient layer in a single continuous film layer.
[0006] This invention utilizes a heterogeneous design of different oxide materials in the antireflective coating solution and a physical sedimentation mechanism to form a gradual change in refractive index within a single film layer. This differs from existing methods that rely on multilayer film coating to form a gradual change in refractive index, and overcomes the problems of interlayer separation and interlayer interface demarcation that easily lead to the effect of light transmittance caused by multilayer film coating.
[0007] Furthermore, an antireflective coating solution for photovoltaic glass comprises the following components by mass fraction: 1.0-8.0% binder, 0.1-2.0% leveling agent, 3.0-15.0% oxide material, and the balance being solvent.
[0008] Furthermore, an antireflective coating liquid for photovoltaic glass: the mass ratio of the first oxide material to the second oxide material is (1-10):(1-2).
[0009] Furthermore, an antireflective coating solution for photovoltaic glass: the solvent is selected from one or more combinations of water, ethanol, isopropanol, propylene glycol methyl ether, and ethylene glycol butyl ether; the binder is selected from one or more combinations of silicates, phosphates, polysilazane, and organosilicon resins; and the leveling agent is selected from polyether-modified organosilicon leveling agents or fluorocarbon-modified polyacrylate leveling agents.
[0010] Furthermore, an antireflective coating liquid for photovoltaic glass: the first oxide material and the second oxide material are respectively selected from at least one of silicon oxide, aluminum oxide, titanium oxide, and zirconium oxide.
[0011] Furthermore, an antireflective coating liquid for photovoltaic glass: the first oxide material and / or the second oxide material are hollow microspheres with cavities inside, the wall thickness of the hollow microspheres is 10-60 nm and the particle size is 20-200 nm, and the cavity in the hollow microspheres accounts for 30-85% of the overall volume.
[0012] Furthermore, an antireflective coating liquid for photovoltaic glass: the first oxide material and / or the second oxide material are solid microspheres with pores on the surface, and the particle size of the solid microspheres is 15-80 nm.
[0013] Furthermore, an antireflective coating liquid for photovoltaic glass: the pores on the surface of the first oxide material and / or the second oxide material are formed by creating pores with a pore-forming agent, wherein the pore-forming agent is selected from polyacrylic acid particles.
[0014] The present invention also provides a coated glass with a gradient film layer, the coated glass comprising a glass substrate and an antireflective film layer formed on the surface of the glass substrate, the antireflective film layer being formed by curing the aforementioned antireflective coating solution, the thickness of the antireflective film layer being 80-300 nm, the refractive index of the antireflective film layer decreasing in the thickness direction from the glass substrate to the air interface, the refractive index being 1.4-1.48 near the glass substrate side and 1.20-1.32 near the air side.
[0015] The present invention also provides a method for preparing coated glass with a gradient film layer, the method comprising the following steps: S1. The antireflective coating liquid is applied to the surface of the glass substrate by roller coating, slot coating or spraying to form a wet film; S2. Place the coated glass substrate at 15-40°C and 40-80% relative humidity for 30-300 seconds to utilize the difference in gravitational settling rate of the oxide materials to spontaneously arrange them in a gradient in the wet film thickness direction. S3. After the glass substrate has been left to stand, heat and cure it at 250-650°C for 2-30 minutes to obtain coated glass with a gradient film layer.
[0016] Specifically, this invention benefits from the optimized formulation of the coating solution, which allows for a single-coating process during the coating process. By utilizing the density differences between oxide materials with different porosities or particle sizes in the coating solution, the materials spontaneously undergo gravity settling and gradient arrangement during the static setting of the wet film and solvent evaporation after coating. After curing, an antireflective film layer with a gradually changing refractive index is obtained, without the need to apply different coating solutions multiple times to form a composite antireflective film layer structure with a gradually changing refractive index. This not only simplifies the process and increases efficiency but also avoids interlayer demarcation.
[0017] The beneficial effects of this invention are: This invention introduces two or more oxide materials with different physical properties (density, particle size) into the antireflective coating solution. Utilizing the difference in settling rates, the oxide materials with higher density and / or larger particle size (typically having a higher refractive index) settle rapidly and accumulate near the bottom of the glass substrate; while the oxide materials with lower true density and / or smaller particle size (typically having a lower refractive index) settle slowly, are displaced, and remain on the upper layer of the wet film. During the subsequent curing process, this gradient structure from high-refractive-index particles to low-refractive-index particles, formed by gravity, is fixed in situ by the binder, creating a mechanically integrated refractive index gradient layer within a single continuous film. This eliminates the need to construct a composite antireflective coating structure with a refractive index gradient from multiple films, thereby eliminating the problems of easy delamination between multilayer films and the resulting interlayer interface demarcation that affects the appearance and light transmittance of the coated glass.
[0018] This invention achieves a precise correlation between the difference in the settling rate of oxide materials and the difference in refractive index by selecting first and second oxide materials with different densities and particle sizes in the antireflective coating solution formulation and optimizing the density and particle size relationship between the first and second oxide materials. This results in the following excellent effects: ① A single coating and single-layer film can achieve a film structure with a gradually changing refractive index gradient, increasing glass transmittance by more than 3%; ② The film layer is a continuous whole without interfaces and with gradually changing components, exhibiting extremely low internal stress, strong adhesion, and excellent weather resistance, resistance to damp heat, and salt spray resistance; ③ It allows for flexible design of the refractive index gradient distribution curve within the range of 1.20 to 1.48, meeting the needs of different products. Detailed Implementation
[0019] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. The following description of at least one exemplary embodiment is merely illustrative and is in no way intended to limit the present invention or its application or use. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0020] Example 1
[0021] This embodiment 1 provides an antireflective coating solution for photovoltaic glass, which includes 5.0% binder (selected as polysilazane), 2.0% leveling agent (selected as polyether modified organosilicon leveling agent), 9.0% oxide material, and the balance solvent (selected as isopropanol). The oxide material comprises a first oxide material and a second oxide material with different densities and particle sizes, wherein the mass ratio of the first oxide material to the second oxide material is 5:2. Specifically, the first oxide material is hollow alumina microspheres with internal cavities, having an average particle size D1 of approximately 85 nm, a hollow volume ratio of approximately 62%, a density ρ1 of approximately 2.4 g / cm³, and a refractive index of 1.42. The second oxide material is hollow silica microspheres with internal cavities, having an average particle size D2 of approximately 50 nm, a hollow volume ratio of approximately 60%, a density ρ2 of approximately 1.2 g / cm³, and a refractive index of 1.25. The densities ρ1 and ρ2 of the first oxide material satisfy |ρ1 - ρ2| = 1.2 g / cm³. 3 The average particle size D1 of the first oxide material and the average particle size D2 of the second oxide material satisfy D1 / D2=1.7.
[0022] The antireflective coating solution of Example 1 was used to prepare coated glass with a gradient film layer. The coated glass includes a glass substrate and an antireflective film layer formed on the surface of the glass substrate. The antireflective film layer is formed by curing the antireflective coating solution of Example 1. The thickness of the antireflective film layer is 120 nm. The refractive index of the antireflective film layer decreases in a gradient direction from the glass substrate to the air interface. The refractive index near the glass substrate is 1.4 to 1.48, and the refractive index near the air is 1.20 to 1.32. Specifically, the method for preparing coated glass with a gradient film layer includes the following specific steps: S1. Take an ultra-white rolled photovoltaic glass substrate with a thickness of about 2.0 mm, clean and dry it, and then uniformly apply the anti-reflection coating liquid of Example 1 to the surface of the glass substrate by spraying to form a wet film; wherein, the spraying pressure is 0.4 MPa and the spraying distance is 20 cm. S2. Let the coated glass substrate stand for 30 seconds to allow the denser first oxide material to settle towards the glass substrate side and the less dense second oxide material to accumulate towards the air side. Then, let it stand for another 120 seconds at 20°C and 60% relative humidity to utilize the difference in the gravitational settling rate of the oxide materials to allow them to spontaneously arrange themselves in a gradient in the direction of wet film thickness. S3. After the glass substrate has been left to stand, heat it at 600°C for 5 minutes to obtain coated glass with a gradient film layer.
[0023] Tests showed that the average transmittance of the coated glass prepared above reached 94.8% in the wavelength range of 300-1100nm (the transmittance of the uncoated glass substrate is about 91.5%), which is about 1.0% higher than the transmittance gain of the current single-layer antireflective film (not exceeding 2.5%). The adhesion of the antireflective film layer of the present invention can reach level 0 (100-grid test) and the hardness can reach 3H (pencil hardness test).
[0024] Example 2
[0025] This embodiment 2 provides an antireflective coating solution for photovoltaic glass. The coating solution comprises 1.5% binder (selected as silicone resin), 0.2% leveling agent (selected as fluorocarbon modified polyacrylate leveling agent), 3.0% oxide material, and the balance being a solvent (a mixture of isopropanol and water). The oxide material includes a first oxide material and a second oxide material with different densities and particle sizes, with a mass ratio of 1:1. Specifically, the first oxide material is solid silica microspheres with an average particle size D1 of approximately 30 nm, a density ρ1 of approximately 2.2 g / cm³, and a refractive index of 1.46. The second oxide material is hollow silica microspheres with internal cavities, with an average particle size D2 of approximately 120 nm, a density ρ2 of approximately 1.1 g / cm³, and a refractive index of 1.23. The densities ρ1 and ρ2 of the first and second oxide materials satisfy |ρ1 - ρ2| = 1.1 g / cm³. 3 The average particle size D1 of the first oxide material and the average particle size D2 of the second oxide material satisfy D1 / D2 = 0.25.
[0026] The antireflective coating solution of Example 2 was used to prepare coated glass with a gradient film layer. The coated glass includes a glass substrate and an antireflective film layer formed on the surface of the glass substrate. The antireflective film layer is formed by curing the antireflective coating solution of Example 2. The thickness of the antireflective film layer is 300 nm. The refractive index of the antireflective film layer decreases in a gradient from the glass substrate to the air interface in the thickness direction. The refractive index near the glass substrate side is 1.4 to 1.48, and the refractive index near the air side is 1.20 to 1.32. Specifically, the method for preparing coated glass with a gradient film layer includes the following specific steps: S1. Take an ultra-white rolled photovoltaic glass substrate with a thickness of about 2.0 mm, clean and dry it, and then uniformly apply the anti-reflection coating liquid of Example 2 to the surface of the glass substrate by spraying to form a wet film; wherein, the spraying pressure is 0.4 MPa and the spraying distance is 20 cm. S2. Let the coated glass substrate stand for 30 seconds to allow the denser first oxide material to settle towards the glass substrate side and the less dense second oxide material to accumulate towards the air side. Then, let it stand for another 60 seconds at 35°C and 40% relative humidity to utilize the difference in the gravitational settling rate of the oxide materials to allow them to spontaneously arrange themselves in a gradient in the direction of wet film thickness. S3. After the glass substrate has been left to stand, heat it at 500°C for 20 minutes to obtain coated glass with a gradient film layer.
[0027] Tests showed that the average transmittance of the coated glass prepared above reached 94.7% in the wavelength range of 300-1100nm (the transmittance of the uncoated glass substrate is about 91.5%), which is about 1.0% higher than the transmittance gain of the current single-layer antireflective film (not exceeding 2.5%). The adhesion of the antireflective film layer of the present invention can reach level 0 (100-grid test) and the hardness can reach 3H (pencil hardness test).
[0028] Example 3
[0029] This embodiment 3 provides an antireflective coating solution for photovoltaic glass. The coating solution comprises 8.0% binder (using polysilazane), 1.5% leveling agent (using fluorocarbon-modified polyacrylate leveling agent), 15.0% oxide material, and the balance solvent (using a mixture of ethanol and propylene glycol monomethyl ether). An additional 5% by weight of polyacrylic acid latex particles with a particle size of approximately 80 nm is added as a pore-forming agent. During the subsequent heating and curing process of the coating solution, the polyacrylic acid particles decompose, forming pores on the oxide. The oxide material includes a first oxide with different densities and particle sizes. The first oxide material and the second oxide material are used, with a mass ratio of 1:2. Specifically, the first oxide material is hollow titanium dioxide microspheres with an average particle size D1 of approximately 50 nm, a density ρ1 of approximately 2.2 g / cm³, and a refractive index of 1.48. The second oxide material is solid silica microspheres with porous surfaces, with an average particle size D2 of approximately 75 nm, a density ρ2 of approximately 1.8 g / cm³, and a refractive index of 1.25. The densities ρ1 and ρ2 of the first oxide material and the second oxide material satisfy |ρ1 - ρ2| = 0.4 g / cm³. 3 The average particle size D1 of the first oxide material and the average particle size D2 of the second oxide material satisfy D1 / D2 = 0.67.
[0030] The antireflective coating solution of Example 3 was used to prepare coated glass with a gradient film layer. The coated glass includes a glass substrate and an antireflective film layer formed on the surface of the glass substrate. The antireflective film layer is formed by curing the antireflective coating solution of Example 3. The thickness of the antireflective film layer is 230 nm. The refractive index of the antireflective film layer decreases in a gradient from the glass substrate to the air interface in the thickness direction. The refractive index near the glass substrate side is 1.4 to 1.48, and the refractive index near the air side is 1.20 to 1.32. Specifically, the method for preparing coated glass with a gradient film layer includes the following specific steps: S1. Take an ultra-white rolled photovoltaic glass substrate with a thickness of about 2.0 mm. After cleaning and drying, apply the anti-reflection coating liquid of Example 3 evenly to the surface of the glass substrate by spraying to form a wet film; spraying pressure 0.4 MPa, spraying distance 20 cm. S2. Let the coated glass substrate stand for 30 seconds to allow the polyacrylic acid particles to form a concentration gradient distribution, and then continue to stand for 300 seconds at 25°C and 70% relative humidity. S3. After the glass substrate has been left to stand, heat it at 350°C for 25 minutes to obtain coated glass with a gradient film layer.
[0031] Tests showed that the average transmittance of the coated glass prepared above reached 94.6% in the wavelength range of 300-1100nm (the transmittance of the uncoated glass substrate is about 91.5%), which is about 1.0% higher than the transmittance gain of the current single-layer antireflective film (not exceeding 2.5%). The adhesion of the antireflective film layer of the present invention can reach level 0 (100-grid test) and the hardness can reach 3H (pencil hardness test).
[0032] Example 4
[0033] This embodiment 4 provides an antireflective coating solution for photovoltaic glass, which includes 5.0% binder (selected as polysilazane), 2.0% leveling agent (selected as polyether modified organosilicon leveling agent), 9.0% oxide material, and the balance solvent (selected as isopropanol). The first oxide material comprises hollow alumina microspheres with internal cavities, having an average particle size D1 of approximately 65 nm, a hollow volume ratio of approximately 25%, a density ρ1 of approximately 2.4 g / cm³, and a refractive index of 1.42. The second oxide material comprises hollow silica microspheres with internal cavities, having an average particle size D2 of approximately 60 nm, a hollow volume ratio of approximately 60%, a density ρ2 of approximately 1.2 g / cm³, and a refractive index of 1.25. The densities ρ1 and ρ2 of the first and second oxide materials satisfy |ρ1 - ρ2| = 1.2 g / cm³. 3 The average particle size D1 of the first oxide material and the average particle size D2 of the second oxide material satisfy D1 / D2 = 1.08, which does not meet the requirements.
[0034] Comparative Example 1
[0035] The difference between Comparative Example 1 and Example 1 is that the first oxide material in Comparative Example 1 is hollow silicon oxide with an average particle size D1 = 62 nm, a hollow volume ratio of 28%, a true density of 2.3 g / cm³ (ρ1 = 2.3 g / cm³), and a refractive index of 1.41; while the second oxide material in Comparative Example 1 is hollow aluminum oxide with an average particle size D2 = 65 nm, a hollow volume ratio of 25%, a density ρ2 of approximately 2.4 g / cm³, and a refractive index of 1.42. That is, the density difference between the first oxide material and the second oxide material used in Comparative Example 1 is: |ρ1 - ρ2| = 0.1 g / cm³. 3 The condition does not satisfy |ρ1-ρ2|≥0.2g / cm³. 3 Meanwhile, the average particle size ratio between the first oxide material and the second oxide material is D1 / D2 = 0.95, which does not meet the requirement that D1 / D2 ≥ 1.5 or ≤ 0.67.
[0036] Comparative Example 2
[0037] Using the existing double-layer sequential coating process, a bottom coating solution (high refractive index) and a top coating solution (low refractive index) are prepared separately. The bottom layer is first rolled and pre-cured at 150°C for 30 seconds, then the top layer is rolled, and finally tempered at 650°C to obtain coated glass. The production process of Comparative Example 2 has an extra coating step, which increases the time required. Moreover, the two layers are prone to interlayer interface separation, which affects the appearance and light transmittance.
[0038] test: The performance test results of the coated glasses in Examples 1-4 and Comparative Examples 1-2 are shown in the table below:
[0039] The transmittance gain in the table above refers to the increase in transmittance of the coated glass in Examples 1-4 and Comparative Examples 1-2 compared to the glass substrate. The results from Example 1 and Comparative Example 1 show that when the true density difference between the two oxide materials in the coating solution is below the critical value and the particle size ratio does not meet the requirements, the gravity sedimentation separation driving force for film formation disappears, the gradient structure cannot be formed, and the transmittance gain effect decreases significantly.
[0040] The antireflective coating solution provided by this invention can prepare a gradient refractive index antireflective film with excellent comprehensive performance in a single coating process. This simplifies the existing process of forming gradient refractive index film layers, which requires multiple coatings. It not only improves process efficiency, but more importantly, the single coating process can eliminate the need for traditional multiple coatings, directly avoiding the problem of interface boundaries between film layers and ensuring the appearance and light transmittance of the coated glass.
[0041] The antireflective coating solution provided by this invention forms a coated glass in which the refractive index of the antireflective coating layer gradually decreases along the thickness direction from the glass side to the air side. The antireflective coating solution of this invention only requires a single coating to achieve a gradient refractive index film structure, resulting in a simple and low-cost process. The coated glass exhibits excellent antireflective properties and durability over a wide spectral range. Thanks to the optimized antireflective coating solution, the following can be achieved: ① A single coating can form a refractive index gradient film. By limiting the density and particle size differences of the oxide materials themselves, a continuous gradient change in the refractive index within the film layer can be achieved in a single coating process, without the need for multiple coatings or vacuum deposition equipment, making the process simple and efficient; ② The refractive index of the film layer transitions smoothly from the glass side to the air side, eliminating the abrupt refractive index interface, and exhibiting excellent antireflective effects in a wide spectral range of 300–1100 nm; ③ The refractive index of the film layer changes continuously and gradually, without physical delamination interfaces, avoiding the interlayer stress concentration and delamination problems common in multilayer films, resulting in strong adhesion and good wear resistance, while ensuring that the appearance and light transmittance of the coated glass are not affected by delamination interfaces; ④ By optimizing and controlling the density and particle size differences of different oxide materials, gradient distribution curves can be flexibly designed within the refractive index range of 1.20–1.48 to meet the needs of different products.
[0042] The above-described preferred embodiments of the present invention are for illustrative purposes only and are not intended to limit the scope of the invention. Any obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. An antireflective coating liquid for photovoltaic glass, characterized in that, The coating solution includes a solvent, a film-forming component, and an oxide material dispersed in the solvent; The film-forming component includes a binder and a leveling agent, and the oxide material includes at least a first oxide material and a second oxide material with different densities and / or particle sizes. The densities ρ1 of the first oxide material and ρ2 of the second oxide material satisfy |ρ1-ρ2|≥0.2g / cm³ 3 And / or the average particle size D1 of the first oxide material and the average particle size D2 of the second oxide material satisfy D1 / D2≥1.5 or≤0.67, the first oxide material and the second oxide material also have different refractive indices, the refractive indices of the first oxide material and the second oxide material are 1.20~1.48 respectively.
2. The antireflective coating liquid for photovoltaic glass according to claim 1, characterized in that, The coating solution comprises the following components by mass fraction: The composition includes 1.0–8.0% adhesive, 0.1–2.0% leveling agent, 3.0–15.0% oxide material, and the balance being solvent.
3. The antireflective coating liquid for photovoltaic glass according to claim 1, characterized in that, The mass ratio of the first oxide material to the second oxide material is (1-10):(1-2).
4. The antireflective coating liquid for photovoltaic glass according to claim 1, characterized in that, The solvent is selected from one or more combinations of water, ethanol, isopropanol, propylene glycol methyl ether, and ethylene glycol butyl ether; the binder is selected from one or more combinations of silicates, phosphates, polysilazane, and organosilicon resins; and the leveling agent is selected from polyether-modified organosilicon leveling agents or fluorocarbon-modified polyacrylate leveling agents.
5. The antireflective coating liquid for photovoltaic glass according to claim 1, characterized in that, The first oxide material and the second oxide material are each selected from at least one of silicon oxide, aluminum oxide, titanium oxide, and zirconium oxide.
6. The antireflective coating liquid for photovoltaic glass according to claim 1, characterized in that, The first oxide material and / or the second oxide material are hollow microspheres with cavities inside. The hollow microspheres have a wall thickness of 10-60 nm and a particle size of 20-200 nm. The cavities in the hollow microspheres account for 30-85% of the total volume.
7. The antireflective coating liquid for photovoltaic glass according to claim 1, characterized in that, The first oxide material and / or the second oxide material are solid microspheres with pores on their surface, and the particle size of the solid microspheres is 15-80 nm.
8. The antireflective coating liquid for photovoltaic glass according to claim 7, characterized in that, The pores on the surface of the first oxide material and / or the second oxide material are formed by a pore-forming agent, wherein the pore-forming agent is selected from polyacrylic acid particles.
9. A coated glass with a gradient film layer, characterized in that, The coated glass includes a glass substrate and an antireflective coating layer formed on the surface of the glass substrate. The antireflective coating layer is formed by curing the antireflective coating liquid according to any one of claims 1 to 8. The thickness of the antireflective coating layer is 80 to 300 nm. The refractive index of the antireflective coating layer decreases in a gradient from the glass substrate to the air interface in the thickness direction. The refractive index near the glass substrate side is 1.4 to 1.48, and the refractive index near the air side is 1.20 to 1.
32.
10. The method for preparing coated glass with a gradient film layer according to claim 9, characterized in that, The method includes the following steps: S1. The antireflective coating liquid is applied to the surface of the glass substrate by roller coating, slot coating or spraying to form a wet film; S2. Place the coated glass substrate at 15-40°C and 40-80% relative humidity for 30-300 seconds to utilize the difference in gravitational settling rate of the oxide materials to spontaneously arrange them in a gradient in the wet film thickness direction. S3. After the glass substrate has been left to stand, heat and cure it at 250-650°C for 2-30 minutes to obtain coated glass with a gradient film layer.
Citation Information
Patent Citations
Coating liquid and preparation method thereof, photovoltaic glass and solar cell
CN117285834A